ОПТИМІЗАЦІЯ ЕНЕРГОДИНАМІЧНИХ ПРОЦЕСІВ В СИСТЕМАХ ЕЛЕКТРОПРИВОДУ КВАДРОКОПТЕРА - Денисов, Ю.О.; Войтенко, В.П.; Городній, О.М.; Димерець, А.В. (Інститут електродинаміки Національної академії наук України, 2020)
In order to save energy consumption of the battery for powering the quadrocopter flight stabilization system, it is proposed to optimize the process of current consumption by rotor electric drives, which are based on brushless DC motors. They are powered by autonomous voltage inverters. References 10, figures 6.